Cost-Benefit Analysis and the Environment - Atkinson, Giles (OECD Environment Working Papers, 2015)
While the basic principles of cost-benefit analysis (CBA) are long-standing, the challenges entailed in applying these principles are constantly evolving. This paper reviews recent developments in environmental CBA since the publication of an OECD volume on this topic by Pearce et al. (2006). The character and direction of these developments also evolves over time and the current review reflects this process